2007
DOI: 10.1038/sj.bjc.6603552
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor expression as a possible determinant of thromboembolism in ovarian cancer

Abstract: Ovarian cancer, and clear cell carcinoma in particular, reportedly increases the risk of venous thromboembolism (VTE). However, the mechanisms remain unclear. Tissue factor (TF) supposedly represents a major factor in the procoagulant activities of cancer cells. The present study examined the involvement of TF expression in VTE for patients with ovarian cancer. Subjects comprised 32 consecutive patients (mean age 49.8 years) with histologically confirmed ovarian cancer. Presence of VTE was examined using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 29 publications
(29 reference statements)
7
117
0
4
Order By: Relevance
“…Two recent studies have shown that tissue factor (TF) expression by tumor cells may be predictive of systemic VTE in patients with pancreatic and ovarian cancer (50,51). Tumor cells in HCC also have been shown to express TF (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have shown that tissue factor (TF) expression by tumor cells may be predictive of systemic VTE in patients with pancreatic and ovarian cancer (50,51). Tumor cells in HCC also have been shown to express TF (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, clear cell histology was a risk factor for both preoperative silent DVT and PTE in ovarian cancer patients. Very recently, we used immunohistochemical methods to reveal that clear cell adenocarcinoma shows significantly stronger expression of tissue factor, a major factor in the procoagulant activities of cancer cells, compared to nonclear cell adenocarcinoma (Uno et al, 2007). Massive ascites was also an independent and significant risk factor for preoperative DVT in ovarian cancer.…”
Section: Thromboembolism In Ovarian Cancer T Satoh Et Almentioning
confidence: 99%
“…TF, also called thromboplastin, factor III, or CD142, is aberrantly expressed in many types of cancers, including non-small cell lung cancer (5), colorectal cancer (6), genito-urethal (7,8), and gynecologic cancers (9)(10)(11), pancreatic cancer (12), head and neck cancer (13), glioma (14), and metastatic breast cancer (15). Under physiologic conditions, TF is expressed by fibroblasts, pericytes, and smooth muscle cells in the subendothelial vessel wall.…”
Section: Introductionmentioning
confidence: 99%